Hubungan Komitmen Organisasi dengan Perilaku Kerja Inovatif: Tinjauan Sistematis dalam 5 Tahun Terakhir - Dewita, Aurellya Rahmada; Suryanto, Suryanto (Ekonomis: Journal of Economics and Business, 2024)
The novelty of this systematic review is that it attempts to add to the literature review, where no other study has conducted a broad and systematic review of the relationship between Organizational Commitment (OC) and Innovative Work Behavior (IWB). Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology, a total of 26 studies meeting the eligibility criteria were chosen for examination, and the results of these studies were summarized. The review showed that there are three domains that are antecedents of employees’ commitment to innovative behavior. The final outcome of the review indicates OC and IWB also exhibit an indirect impact. The systematic literature review conducted identified a total of 26 studies examining the relationship between OC and IWB from 2018 to June 2023. The majority of these studies focused on industrial organizations (42.3%) and were predominantly conducted in Asian regions (69.1%). All of the studies utilized quantitative research methods (100%), with a significant proportion of the analysis conducted at the individual level (92%).